Eshelby Twist as a Possible Source of Lattice Rotation in a Perfectly Ordered Protein/Silica Structure Grown by a Simple Organism. Issue 42 (14th September 2015) - Zlotnikov, Igor; Werner, Peter; Fratzl, Peter; Zolotoyabko, Emil
Abstract : The formation mechanism of a perfectly ordered protein/silica structure in the axial filament of the anchor spicule of the silica sponge Monorhaphis chuni is suggested. Experimental evidence shows that the growth of this architecture is realized by a thermodynamically driven dislocation‐mediated spiral growth mechanism, resulting in a specific rotation of the mesoscopic crystal lattice (Eshelby twist).